Investigating the potential for battery energy storage system in distributed photovoltaic generation on public buildings in Brazil - Pinto, Gustavo Xavier de Andrade (2024)
Tese (doutorado) ? Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Civil, Florianópolis, 2024.